Testing the Limits of Anaphoric Distance in Classical Arabic: A Corpus-Based Study - Jarbou, Samir O.; Migdadi, Fathi (Research in Language, 2012)
One of the central aims in research on anaphora is to discover the factors that determine the choice of referential expressions in discourse. Ariel (1988; 2001) offers an Accessibility Scale where referential expressions, including demonstratives, are categorized according to the values of anaphoric (i.e. textual) distance that each of these has in relation to its antecedent. The aim of this paper is to test Ariel’s (1988; 1990; 2001) claim that the choice to use proximal or distal anaphors is mainly determined by anaphoric distance. This claim is investigated in relation to singular demonstratives in a corpus of Classical Arabic (CA) prose texts by using word count to measure anaphoric distance. Results indicate that anaphoric distance cannot be taken as a consistent or reliable determinant of how anaphors are used in CA, and so Ariel’s claim is not supported by the results of this study. This also indicates that the universality of anaphoric distance, as a criterion of accessibility, is defied.